Diurnal attraction of fruit flies (diptera: tephritidae) to methyl eugenol in a village ecosystem in Tanjung Bungah, Penang, Malaysia - Wee, Suk Ling; Hee, Alvin Kah-Wei (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Diurnal rhythm of male Bactrocera fruit fly attraction to methyl eugenol (ME) was investigated using clear traps design in a village ecosystem in Tanjung Bungah, Penang, Malaysia. The diurnal rhythm pattern studied by half-hourly sampling from 07:00 to 18:00 hr showed significant male fruit fly attraction to ME in the morning from 07:30 to 09:30 hr, with a distinct peak at 08:30-09:00 hr. The male attraction to ME was significantly lower in the afternoon and remained low approaching late afternoon. The ME-responding fruit fly species captured were B. dorsalis (86%), which dominated the local Bactrocera community, followed by B. umbrosa (5.8%) and B. carambolae (0.1%). This showed that B. dorsalis is a more dominant species than its sibling species, B. carambolae in the area studied. In addition, ca. 8.1% of Bactrocera male flies that bore intermediate morphological characteristics between B. dorsalis and B. carambolae were also captured in those traps. The present study shows that for ME-responding Bactrocera spp., male attraction to ME occurs throughout the day with peak period of attraction to ME occurring ca. 30 mins following sunrise for 2 hrs before gradually tapering off.